Tropical fruit vinegars - Zul Ariff Abdul Latiff; Seri Intan Mokhtar; Mohammad Amizi Ayob (Penerbit Universiti Malaysia Kelantan, 2019)
Tropical vinegar has health foods that give benefit to the life of man. The book begins the detail of vinegar from production, processing and marketing. Furthermore the benefits of vinegar in terms of nutritional value are described in the book. The book emphasizes the important criteria and application of vinegar in daily consumption. Lastly, several real case studies are included in the book.